1995
DOI: 10.1074/jbc.270.42.24995
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Transcription Factor NF-κB Is Suppressed by Curcumin (Diferuloylmethane)

Abstract: When activated, NF-B, a ubiquitous transcription factor, binds DNA as a heterodimeric complex composed of members of the Rel/NF-B family of polypeptides. Because of its intimate involvement in host defense against disease, this transcription factor is an important target for therapeutic intervention. In the present report we demonstrate that curcumin (diferuloylmethane), a known anti-inflammatory and anticarcinogenic agent, is a potent inhibitor of NF-B activation. Treatment of human myeloid ML-1a cells with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

30
883
1
6

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,279 publications
(941 citation statements)
references
References 45 publications
(40 reference statements)
30
883
1
6
Order By: Relevance
“…Curcumin is a dietary compound with the known properties of antioxidation, anti-in¯ammation, and anticarcinogenesis (Huang et al, 1994;1988;Rao et al, 1995;Ruby et al, 1995;Singh and Aggarwal, 1995). Curcumin blocks c-jun expression and NF-kB activation induced by various agents (Hanazawa et al, 1993;Huang et al, 1991;Singh and Aggarwal, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Curcumin is a dietary compound with the known properties of antioxidation, anti-in¯ammation, and anticarcinogenesis (Huang et al, 1994;1988;Rao et al, 1995;Ruby et al, 1995;Singh and Aggarwal, 1995). Curcumin blocks c-jun expression and NF-kB activation induced by various agents (Hanazawa et al, 1993;Huang et al, 1991;Singh and Aggarwal, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The anticarcinogenic e ects of this compound are demonstrated by its ability to inhibit tumor initiation by azoxymethane, benzpyrene and 7,12-dimethyl-benz(a)anthracene, and to suppress tumor promotion by phorbol esters (Huang et al, 1994(Huang et al, , 1988Rao et al, 1995). It has been shown that curcumin strongly inhibits both c-Jun and NF-kB activation by PMA or tumor necrosis factor-a (TNF-a) treatments (Hanazawa et al, 1993;Huang et al, 1991;Singh and Aggarwal, 1995). This inhibitory e ect may account for the anti-in¯ammatory and anti-oxidant properties of curcumin (Ruby et al, 1995;Singh and Aggarwal, 1995); however, the mechanism of these inhibitory e ects remains unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In studies of the myeloid cell line ML-1a, Singh and Aggarwal reported that curcumin inhibited IkBa phosphorylation, degradation, and NF-kB translocation induced by a diverse range of stimuli including TNF, hydrogen peroxide, and phorbol esters [2]. Subsequent studies confirmed curcumininduced inhibition of NF-kB translocation in multiple cell types, including colon [3], gastric [4], pancreatic [5], and squamous epithelial tumor cell lines [6] as well as B-cell lymphoma and multiple myeloma cell lines [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18] In addition, synthetic double-stranded DNA (dsDNA) with high affinity for NFkB, NFkB decoy, have been shown to block the induction of gene expression mediated by NFkB in vitro 15,[19][20][21][22] and in vivo. 23,24 With the use of decoy oligonucleotides, the function of a particular DNA-binding protein or protein complex can be inhibited since the decoy competes for protein binding with the authentic binding elements, interfering with gene regulation.…”
Section: Introductionmentioning
confidence: 99%